Contracting with third parties - Sandeep Baliga; Tomas Sjöström (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2005)
In the bilateral hold-up model and the moral hazard in teams model, introducing a third party allows implementation of the first-best outcome, even if the agents can renegotiate inefficient outcomes and collude. Fines paid to the third party provide incentives for truth-telling and first-best levels of investment. Our results suggest that models that provide foundations for hold-up and incomplete contracts by invoking renegotiation are sensitive to the introduction of third parties.
Keywords: 330